Legal Protection of Social Security BPJS Employment for Informal Workers - Agustin Meilarovasari; Fajar Rachmad Dwi Miarsa; Dhofirul Yahya (Journal of Law, Politic and Humanities, 2025)
This research discusses the legal protection for social security in employment for informal workers as a realization of the mandate of the state basis of the Republic of Indonesia aimed at achieving social welfare. The objective of this research is to identify the forms of legal protection for participants of social security in employment from the ranks of informal workers, as well as solutions to the problems that arise, particularly related to the inability to pay contributions to BPJS Ketenagakerjaan. The research method used is normative juridical with a legislative approach (statute approach). The data sources utilized are derived from primary and secondary legal materials, with data collection techniques through literature study. Data analysis is conducted in a descriptive-analytical manner. The problem formulations in this research include: (1) What is the form of legal protection for informal workers in employment social security, and (2) What are the legal consequences for informal workers who are unable to pay the BPJS Employment contributions.